2021
DOI: 10.1002/aenm.202102016
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying and Suppressing Proton Intercalation to Enable High‐Voltage Zn‐Ion Batteries

Abstract: Rechargeable Zn‐ion batteries (ZIBs) are widely regarded as promising candidates for large‐scale energy storage applications. Like most multivalent battery systems (based on Zn, Mg, Ca, etc.), further progress in ZIB development relies on the discovery and design of novel cathode hosts capable of reversible Zn2+ (de)intercalation. Herein, this work employs VPO4F as a ZIB cathode and explores ensuing intercalation mechanisms along with interfacial dynamics during cycling to quantify the water dynamics in concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 59 publications
1
49
0
Order By: Relevance
“…The proton-intercalation host VPO 4 F could be simply synthesized by the electrochemical extraction of Li + ions from LiVPO 4 F under galvanostatic conditions with careful control of the charging potential (Figure S1). [12] However, the VPO 4 F cathode is at an oxidized state that may cause some side reactions, which are not suitable for assembling the electrochemical cell. [13] Since the concentration of protons in the electrolyte is much higher than the extracted Li + , LiVPO 4 F is used as the pristine electrode directly in the following experiments.…”
Section: Introductionmentioning
confidence: 99%
“…The proton-intercalation host VPO 4 F could be simply synthesized by the electrochemical extraction of Li + ions from LiVPO 4 F under galvanostatic conditions with careful control of the charging potential (Figure S1). [12] However, the VPO 4 F cathode is at an oxidized state that may cause some side reactions, which are not suitable for assembling the electrochemical cell. [13] Since the concentration of protons in the electrolyte is much higher than the extracted Li + , LiVPO 4 F is used as the pristine electrode directly in the following experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, a study on developing a high-voltage ZIB by suppressing H + intercalation was recently reported. [61] Polyanion VPO 4 F is a promising cathode, owing to its high operating potential, which accommodates Zn 2 + cations at 1.9 V (vs. Zn/ Zn 2 + ), while most of the overall capacity (> 70 %) is attributed to the proton intercalation below 1.9 V, leading to an unstable high working voltage (Figure 4d). Unfortunately, the intercalation of Zn 2 + and H + is competitive, and the insertion of H + was detrimental, relating to the formation of a layered double hydroxide precipitate on the positive electrode region, which caused a surface impediment and reduced the electrochemical reversibility.…”
Section: Modification On Cation Intercalation Mechanismmentioning
confidence: 99%
“…Table 2 summarizes the as-reported strategies to develop high voltage working cathode materials. [16,18,31,37,58,61,66,[68][69][70][71][72][73][74][75][76] As illustrated in the table, not only intercalating materials, adopting halogen molecules and p-type organic polymers also can provide high working voltage. It should be further CV at different scan rates from 0.1 to 0.9 mV s À 1 .…”
Section: Energy Storage Via Anion Intercalationmentioning
confidence: 99%
“…Besides that, the side reactions especially for hydrogen evolution reaction (HER) would lead to a sharp increment of internal pressure in battery [19][20][21]. While for the vanadium oxide cathode side, from the perspective of storage mechanism, the co-embedding of Zn 2+ /H + into vanadium oxide host and accompanying with the generation of alkali by-product in the cathode/electrolyte interface is the most commonly acknowledged storage mechanism especially in the acidic electrolyte (Zn(OTf) 2 /H 2 O) system [22,23]. Note that such low conductive by-product would not only consume the zinc ions in the electrolyte, but also block the interfacial ion/ electron transport during cycling [24].…”
Section: Introductionmentioning
confidence: 99%